On Constrained Convexity Tomography and Lagrangean Approximations - Aslanyan, L.; Sahakyan, H.; Hovsepyan, A. (Mathematical Problems of Computer Science, 2021)
In this paper one particular problem of general type of discrete tomography problems is considered and an approximate algorithm for its solution based on Lagrangean relaxation is introduced. A program’s implementation is given as well.